The Drell-Yan process at NNLL′+NNLO using rapidity dependent jet vetoes - Thomas Clark; Shireen Gangal; Jonathan R. Gaunt (Journal of High Energy Physics)
Abstract We present results for the Drell-Yan process pp → Z/γ ∗ + X → l + l − + X in the presence of the rapidity dependent jet vetoes T Bj $$ {\mathcal{T}}_{Bj} $$ and T Cj $$ {\mathcal{T}}_{Cj} $$ . These observables provide a tighter veto at central rapidities than at forward rapidities. Our predictions contain a resummation of large logarithms of the veto scale over the hard scale, matched to fixed order in perturbation theory; we present results at both NLL′+NLO and NNLL′+NNLO. Uncertainty estimates are provided that contain both resummation and fixed-order uncertainties; we find that using a standard profile scale variation procedure for the former seems to underestimate the uncertainty, particularly at NLL′+NLO. Consequently, we modify the procedure to avoid cancellation of scale variations between partonic channels, and verify that the uncertainties from this method are reasonable using a simplified version of the Theory Nuisance Parameter (TNP) method. We then find that the uncertainty decreases going from the NLL′+NLO to the NNLL′+NNLO predictions, and obtain an uncertainty at the level of 1 − 3% in the NNLL′+NNLO predictions when the veto scale is of 𝒪(10 GeV).